Korean Drama Constructing Multiculturalism among Muslim Women Students - Okta Nurul Hidayati; M. Endy Saputro (Al-Albab, 2017)
Abstract This paper aims to understand the unique relationship between Korean drama and the formation of multicultural identity among Muslim women students. On the one hand, as a form of racial activity, watching Korean dramas can establish a new form of identity while at the same time enriching a new perspective of building multicultural sense. On the other hand as a part of Muslim, they can control Korean culture that is incompatible with Islamic doctrine. This paper argues that adopting Korean dramas positively supports students in creating multicultural cultures. These findings may contribute to the formation of cultural diversity within the Islamic context.